Scandal at Societe Generale : rogue trader or willing accomplice? - Walker, Russell ([London] : SAGE, 2016)
This case covers the scandal that occurred in 2008 at Societe Generale when one trader, Jerome Kerviel, lost the prominent French bank nearly five billion Euros through his unauthorized trading. The case describes Kerviel's schemes as well as SocGen's internal monitoring and reporting processes, organizational structures, and culture so that students reading the case can identify and discuss the shortcomings of the firm's risk management practices. The case and epilogue also describe the French government's and Finance Minister Christine Lagarde's reactions to the scandal (e.g., imposition of a four million Euros fine and increased regulations), prompting students to consider the role of government in overseeing that healthy risk management practices are followed in key industries (such as banking) that are highly entwined with entire economies.
Originally Published in: Walker, R. (2013). Scandal at Societe Generale: Rogue Trader or Willing Accomplice? (teaching notes revised 01/05/2014). 5-313-505. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Societe generale (France); Risk management -- Case studies